Identification of male-produced aggregation pheromone of the curculionid beetle Acrotomopus atropunctellus. Issue 4 (28th March 2016) - Rodríguez, S.A.; Pérez, M.L.P.; Nazareno, M.A.
Abstract: The sugarcane stem weevil, Acrotomopus atropunctellus (Boheman) (Curculionidae: Molytinae: Cholini) is an important economic pest from the Northwestern region of Argentina. Analyses of the headspace volatiles produced by separated males and females revealed one male-specific compound. Its structural identification is reported here in using gas chromatography coupled with mass spectroscopy analysis and chemical micro-reactions. Besides, two laboratory olfactometry assays allowed us to propose 6-methyl-5-hepten-2-one (sulcatone) as an aggregation pheromone for this insect, being attractive to both conspecific males and females. This compound is reported for the first time as involved in the Curculionidae family communication.